The Decline of Soil Infiltration Capacity Due To High Elevation Groundwater - Isri Ronald Mangangka (Institute of Research and Community Outreach - Petra Christian University, 2008)
Infiltration capacity of soil mainly depends on two factors; the particle size and the moisture content of the soil. Groundwater increases the soil moisture, not only below the water table but also within the capillary zone, above the water table. Field experiment in a high groundwater area was conducted to understand the relationship among the groundwater, soil moisture and infiltration capacity. Using a single ring infiltrometer, the effect of groundwater in the infiltration rate was observed. This field experiment result shows that the groundwater influences significantly the infiltration capacity of the soil, and the infiltration rate follows a specific trendline.